Analysis of renal stones by capillary isotachophoresis - Jarolímová, Zdeňka; Lubal, Přemysl; Kanický, Viktor (Talanta, 2012)
An analytical method for the determination of the composition of renal stones by capillary isotachophoresis with conductometric detection was developed. Using different leading/terminating electrolyte systems, the qualitative and quantitative analysis of organic compounds (urate, xanthate, oxalate) and inorganic ions (phosphate, Ca(2+), Mg(2+), Na(+), NH(4)(+)) species commonly present in mixed renal stones in three separate steps can be carried out with limits of detection about 10 μmol/L. The developed method was validated by the analysis of real samples and can be used for urinary calculi classification. In addition, it was verified that this method can also be employed for the determination of the above mentioned analytes in some other samples (bones, teeth) concerning apatite biominerals (fluoro-, carbonate-, chloro-apatite).
Keywords: Anions; kosti a kostní tkáň; limita detekce; uhličitany; Phosphates; konduktometrie; Conductometry; Kidney Calculi; Humans; kationty jednomocné; Carbonates; kyselina močová; soli; kationty dvojmocné; Limit of Detection; lidé; Cations, Monovalent; Oxalates; oxaláty; anionty; Bone and Bones; Apatites; Uric Acid; apatity; zuby; izotachoforéza; Tooth; fosfáty; Isotachophoresis; Cations, Divalent; Salts; ledvinové kameny